(untitled) (Al-Qamar, 2021)
This article studies the thoughts of Ismāʻīl Rājī al-Fārūqī (1921-1986), a Palestinian-American scholar and philosopher, on the principles of Islamization of modern social sciences. It argues that Modern Western sciences are based on materialism, aimed at profit, luxury and improving living standards. There is no place in these sciences for seeking God and moral values. But there is also no doubt in the fact that number of new practical questions about politics and society, have been addressed by these modern sciences. Al-Fārūqī believes in the use of modern Western sciences, but emphasizes the need to reconcile religious and secular sciences. The essential elements of modern Western sciences that are in conflict with Islamic thought and philosophy should be Islamized and disseminated to the common man. To this end, al-Fārūqī has outlined a number of principles, according to which Muslims have been suggested to come up with such a curriculum by critically analyzing modern Western social sciences in the light of Islamic sciences that meets with the requirements of the modern age as well is compatible with Islamic Sharīʻah.